2013
DOI: 10.1117/1.jbo.18.5.056004
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic lifetime contrast between methylene blue monomers and self-quenched dimers as a model for dual-labeled activatable probes

Abstract: Abstract. Activatable photoacoustic probes efficiently combine the high spatial resolution and penetration depth of ultrasound with the high optical contrast and versatility of molecular imaging agents. Our approach is based on photoacoustic probing of the excited-state lifetime of methylene blue (MB), a fluorophore widely used in clinical therapeutic and diagnostic applications. Upon aggregation, static quenching between the bound molecules dramatically shortens their lifetime by three orders of magnitude. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 47 publications
5
64
0
5
Order By: Relevance
“…In addition to spectral data, Carroll et al detected increased scattering signal 22 , and Morgounova et al detected decreased triplet transient absorption at 660 nm 18 of MB in SDS at premicellar concentrations. This suggested the presence of MB/SDS clusters.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to spectral data, Carroll et al detected increased scattering signal 22 , and Morgounova et al detected decreased triplet transient absorption at 660 nm 18 of MB in SDS at premicellar concentrations. This suggested the presence of MB/SDS clusters.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Morgounova et al measured the difference in PA lifetime contrast between MB monomers and dimers, suggesting potentials for an activatable probe using enzymatic cleavage. 18 PA monitoring of MB can also measure changes in the local tissue environment. Ashkenazi used MB to measure dissolved oxygen in biological tissues because the PA lifetime of MB decreased due to energy transfer to oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Among them there are chemical indicators, markers, and spectral sensitization systems, biocompatible agents for photodynamic therapy [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Static quenching involves aggregation of the MB molecules. MB can form self-quenched dimers that according to Morgounova et al (25) can reduce the excited state lifetime of MB by three orders of magnitude. A report by McCullagh and Robertson (16) found that at higher concentrations, MB formed dimeric compounds also reducing the efficiency of the system.…”
Section: Discussionmentioning
confidence: 99%